2020
DOI: 10.4274/jcrpe.galenos.2019.2019.0082
|View full text |Cite
|
Sign up to set email alerts
|

Macular Variability in Children and Adolescents with Metabolic Syndrome: A Cross-sectional Study Examining the Associations with Anthropometric Measurements, Metabolic Parameters and Inflammatory Markers

Abstract: Macular damage may be observed in obesity and metabolic syndrome (MetS), a condition which leads to chronic subclinical inflammation and affects most organ systems. To investigate the association between macular variability and anthropometric measurements, metabolic parameters, and inflammatory markers in children and adolescents with MetS. Methods: Two hundred and twenty eyes of 62 obese and 48 healthy children and adolescents were examined. Bilateral macular retinal thickness (MRT) and macular retinal volume… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 28 publications
(32 reference statements)
1
6
0
Order By: Relevance
“…This finding means that IR could accelerate retinal neurodegeneration in the early stages of T2DM. Similar tendency was obtained in previous studies with obese or metabolic positive subjects [15,28]. In contrary, another study in patients with a long history of T2DM but no DR found that serum insulin levels and HOMA-IR values correlated inversely with macular microvascular impairment [31].…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…This finding means that IR could accelerate retinal neurodegeneration in the early stages of T2DM. Similar tendency was obtained in previous studies with obese or metabolic positive subjects [15,28]. In contrary, another study in patients with a long history of T2DM but no DR found that serum insulin levels and HOMA-IR values correlated inversely with macular microvascular impairment [31].…”
Section: Discussionsupporting
confidence: 89%
“…All these comorbidities complicate the challenges they face, subsequently causing chronic inflammation, microvascular damage, and oxidative stress. These factors would impair blood supply of microvessels, which in turn leads to oxidative stress and hypoxia in tissues [[15]]. Apoptosis of neural cells and tissue necrosis may then be triggered in the early course of diabetes development [[24]].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some studies have reported that these ocular parameters are significantly decreased in obese children (52,54). In one study, MRT and MRV values tended to be thinner with an increase in BMI-SDS and waist circumference standard deviation score (WC-SDS) (54). However, a clear link between obesity and decreased CT and MRT has not yet been established.…”
Section: The Association Between Choroidal Thickness and Macular Reti...mentioning
confidence: 99%
“…Obesity not only affects CT but also macular retinal thickness (MRT) and macular retinal volume (MRV). Some studies have reported that these ocular parameters are significantly decreased in obese children ( 52 , 54 ). In one study, MRT and MRV values tended to be thinner with an increase in BMI-SDS and waist circumference standard deviation score (WC-SDS) ( 54 ).…”
Section: Introductionmentioning
confidence: 99%